Faecal antibiotic resistome of Nigerian chimpanzees from a wildlife sanctuary in cross-river state, Nigeria (2021)
"Out of prescription, indiscriminate use, misuse and abuse of antibiotic administration and/or usage in both humans and farm animals have led to a consistent interference and contamination of biomes and ecobiomes. These resultantly give platforms for positive selection of resistant pathogens and high levels of Antibiotic Resistance Genes (ARGs). We examined Nigerian Chimpanzees in Boki Afi Mountain Wildlife Sanctuary, Cross-River State, Nigeria, to detect ARGs. Faecal samples from 15 Chimpanzees in pristine enclosures of Non-Human Primates in the Wildlife Sanctuary were analyzed. All faecal samples were pooled, then resuspended in phosphate-buffered saline. Subsequently, nucleic acid was extracted from the suspension and Illumina sequencing performed. ARGs in the raw reads were determined and assembled using the KmerResistance tool v2.2. From the 2,763,954 reads generated, 14 ARGs with statistically significant reads were identified. Precisely, 90.5% (12/14) of the ARGs detected target drugs that inhibit translation, of which 66.6% (8/12) were tetracycline resistance (TC-r) genes, while remaining 9.5% (2/14) inhibit cell wall synthesis (cfxA3_1 and cfxA6_1). Eight (aph(3’)-III_1, cfxA3_1, cfxA6_1, erm(B)_10, tet(Q)_1, tet(Q)_2, tet(Q)_4, tet(W)_5) of the ARGs detected were predicted to be plasmid-borne. We report using a cultivation-independent approach the presence of ARGs in Nigerian Chimpanzees. Findings suggest Nigerian Chimpanzees may constitute a hitherto overlooked source of antibiotic resistance in the environment. These ARGs may have been exchanged with handlers and rural dwellers around the Sanctuary. Surveillance of sympatric human faecal and environmental microbiota and their resistomes at the Wildlife Sanctuary are merited to inform public health interventions and decrease ARGs dissemination."